Cost-effectiveness of center-based compulsory rehabilitation compared to community-based voluntary methadone maintenance treatment in Hai Phong City, Vietnam. (1st November 2016) - Vuong, Thu; Shanahan, Marian; Nguyen, Nhu; Le, Giang; Ali, Robert; Pham, Khue; Vuong, Thu T.A.; Dinh, Thuy; Ritter, Alison
Highlights: The first study comparing methadone treatment with compulsory detention in Asia. Methadone treatment more effective and less costly than compulsory detention. Over 3 years, methadone treatment cost US4108 less for one participant. Over 3 years, an additional 344 drug-free days gained for a methadone participant. Abstract: Introduction: In Vietnam, two dominant approaches for heroin treatment are center-based compulsory rehabilitation (CCT), funded by the Vietnamese government and community-based voluntary methadone maintenance treatment (MMT), funded primarily by international donors. Recent reduction in international funding requires more efficient allocation of government funding for public health programs. A cost-effectiveness analysis comparing two approaches provides a useful source of evidence to inform the government about funding reallocation. Methods: The study was a combined retrospective and prospective, non-randomized cohort comparison over three years of CCT and MMT in Vietnam, conducted between 2012 and 2014, involving 208 CCT participants and 384 MMT participants with heroin dependence. The primary end-point was drug-free days over three years. Total costs, including both program and participant personal costs were measured and cost-effectiveness compared. Mixed effects regression analyses were used to analyze effectiveness data and non-parametric bootstrapping method was used to compare cost-effectiveness. Results: Over three years, MMT costed on average VND85.73 million (US4108) less than CCT (95% CI: -VND76.88 million, -VND94.59 million). On average, a MMT participant had 344.20 more drug-free days compared to a CCT participant (p < 0.001). The incremental cost-effectiveness ratio for MMT was -VND0.25 million (US11.99) (95% CI: -VND0.34 million, -VND0.19 million) per drug-free day suggesting MMT is the more cost effective alternative. Conclusions: Compared to CCT, MMT is both less expensive and more effective in achieving drug-free days. If the government of Vietnam invests in MMT instead of CCT, it is potentially a cost-saving strategy for reducing illicit drug use among heroin dependent individuals.